Sensitivity and Specificity of a Prototype Rapid Diagnostic Test for the Detection of Trypanosoma brucei gambiense Infection: A Multi-centric Prospective Study. - Sylvie Bisser; Crispin Lumbala; Etienne Nguertoum; Victor Kande; Laurence Flevaud; Gedeao Vatunga; Marleen Boelaert; Philippe Büscher; Theophile Josenando; Paul R Bessell; Sylvain Biéler; Joseph M Ndung'u (Public Library of Science (PLoS), 2016)
BACKGROUND:A major challenge in the control of human African trypanosomiasis (HAT) is lack of reliable diagnostic tests that are rapid and easy to use in remote areas where the disease occurs. In Trypanosoma brucei gambiense HAT, the Card Agglutination Test for Trypanosomiasis (CATT) has been the reference screening test since 1978, usually on whole blood, but also in a 1/8 dilution (CATT 1/8) to enhance specificity. However, the CATT is not available in a single format, requires a cold chain for storage, and uses equipment that requires electricity. A solution to these challenges has been provided by rapid diagnostic tests (RDT), which have recently become available. A prototype immunochromatographic test, the SD BIOLINE HAT, based on two native trypanosomal antigens (VSG LiTat 1.3 and VSG LiTat 1.5) has been developed. We carried out a non-inferiority study comparing this prototype to the CATT 1/8 in field settings. METHODOLOGY/PRINCIPAL FINDINGS:The prototype SD BIOLINE HAT, the CATT Whole Blood and CATT 1/8 were systematically applied on fresh blood samples obtained from 14,818 subjects, who were prospectively enrolled through active and passive screening in clinical studies in three endemic countries of central Africa: Angola, the Democratic Republic of the Congo and the Central African Republic. One hundred and forty nine HAT cases were confirmed by parasitology. The sensitivity and specificity of the prototype SD BIOLINE HAT was 89.26% (95% confidence interval (CI) = 83.27-93.28) and 94.58% (95% CI = 94.20-94.94) respectively. The sensitivity and specificity of the CATT on whole blood were 93.96% (95% CI = 88.92-96.79) and 95.91% (95% CI = 95.58-96.22), and of the CATT 1/8 were 89.26% (95% CI = 83.27-93.28) and 98.88% (95% CI = 98.70-99.04) respectively. CONCLUSION/SIGNIFICANCE:After further optimization, the prototype SD BIOLINE HAT could become an alternative to current screening methods in primary healthcare settings in remote, resource-limited regions where HAT typically occurs.